Run for the Border : Vice and Virtue in U.S.-Mexico Border Crossings - Bender, Steven (Book collections on Project MUSE., 2012)
Mexico and the United States exist in a symbiotic relationship: Mexico frequently provides the United States with cheap labour, illegal goods, and, for criminal offenders, a refuge from the law. In turn, the U.S. offers Mexican labourers the American dream: the possibility of a better livelihood through hard work. To supply each other's demands, Americans and Mexicans have to cross their shared border from both sides. Despite this relationship, U.S. immigration reform debates tend to be security-focused and center on the idea of menacing Mexicans heading north to steal abundant American resources. Further, Congress tends to approach reform unilaterally, without engaging with Mexico or other feeder countries, and, disturbingly, without acknowledging problematic southern crossings that Americans routinely make into Mexico.